War on Disease - Jonas Zimmermann (Historia.scribere)
This paper investigates how widespread acceptance of the polio vaccination was generated in the United States. It shows that FDR transformed the struggle against polio into a national endeavor and that the fear of polio contributed to the widespread anticipation of the vaccine. A main focus is placed on the medical researcher Jonas Salk who fostered public trust in the vaccine. This paper will argue that a timely switch from Salk’s inactive vaccine to Sabin’s oral, live vaccine rekindled the national interest in polio and that the war rhetoric on polio further motivated Americans to get vaccinated.